Implementasi Pendekatan Scientific dalam Proses Pembelajaran Fiqih di MI Miftahul Falah Jakenan - Rosyidah, Siti Fariha (Lembaga Yasin AlSys, 2022)
This research is intended to describe the implementation of science in fiqh learning for student activity, obstacles and solutions at MI Miftahul Falah Jakenan. In the implementation of this research apply descriptive type using qualitative methods. The data obtained with qualitative techniques are the results of observations and interviews. Based on the data that has been found, this research will complete the implementation of fiqh learning by implementing it scientifically for student activity which is already going quite well, where the teachers apply let's observe, ask, try, collect problems, associate, and communicate. Through the application of this scientific approach, it means that it can influence the development of students' skills including critical thinking, communication skills, and skills in working together and investigating. Obstacles found in the implementation of scientific learning are in the form of a lack of interest in students and a lack of utilization of existing facilities and infrastructure. The solution that can be done by the school is to seek educators to take part in training and teachers insert the use of learning media on certain materials.